Public Satisfaction to District Integrated Administration Services (PATEN) at Bancak District, Semarang Regency - Fakih, Moh. (Forum Ilmu Sosial, 2021)
In the context of developing and optimizing the role of districts in regional autonomy through improving public services, it is expected that create equitable regional development and provide quality services and public satisfaction. Integrated District Administrative Services (PATEN) as a policy submitted to the district government to improve the quality of public services that must be according to the needs and satisfaction of the people in public service standards. Public satisfaction has been determined by 9 service elements as a measure of the quality of public services. Purpose of this research is to identify the PATEN given by Bancak District, Semarang Regency and satisfaction level of Bancak District people about PATEN in 2019. To achieve the purpose, this research used descriptive qualitative research methods. In achieving the quality-of-service performance at Bancak District cannot be separated from the constraints and efforts made to adjust to the requirements (substantive, administrative, and technical). Public satisfaction from the survey results based on 9 service elements in Public Satisfaction Index shows good service performance and good service quality (B) and also average of satisfaction index to services 3.242. The value of the public satisfaction index after converting is obtained 81.053 (satisfying). Suggestions for increasing public satisfaction include: policies on delegation of authority related to substantive requirements need to be added and reinforced, support and guidance of Human Resource personnel in implementing PATEN, coordination between work units, and PATEN implementers as a whole in charge of the main duties and functions of PATEN.